Analisis Peran Digitalisasi terhadap Kualitas Layanan di Sektor Perbankan - Ratna Arista Dewi; Warsidi; Abdul Aji Kresna Tri Anggara (Veteran Economics, Management, & Accounting Review, 2026)
This study, employing a PRISMA-based Systematic Literature Review (SLR) approach, aims to identify and categorize the key dimensions of digital service quality in the banking sector amidst the shift in customer preferences from physical to digital services. Out of 56 articles initially identified, a rigorous selection process based on inclusion and exclusion criteria was conducted, resulting 11 high reputable scientific articles (Q1 and Q2) published between 2016 and 2025 as the basis for analysis. The results demonstrate that digital banking service quality can be grouped into three main dimensional categories: the technical and system infrastructure dimension (cybersecurity, system reliability, and operational speed); the emotional and socio-contextual experience dimension (convenience, digital brand image, and the autonomy of artificial intelligence/AI features); and the omnichannel integration dimension. Furthermore, this study indicates a methodological shift in bank service quality assessment, moving from conventional, reactive questionnaires toward the proactive utilization of real-time customer review big data driven by machine learning. Consequently, future research is recommended to conduct empirical quantitative testing on app store reviews, while incorporating moderating variables such as digital financial literacy, age, and cyber fraud risks.